The Effect of Online Learning on Learning Interest During The Covid-19 Pandemic - Amelia Warikar; Ali Mustadi; Oktavian Muning Sayekti (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this study was to ascertain students' interest in learning during their time spent online. The method used in this study is ex post facto quantitative research. The population of this study was approximately 307 students, which corresponds to the total number of PGSD fourth-semester students. This study's sample consisted of 40 individuals. A researcher gathered data via a google form questionnaire. The descriptive and inferential data analysis techniques used in this study are descriptive and inferential. The study's findings indicate a 0.562-degree relationship between online study and student interest in learning. This is the degree to which a moderate correlation exists with a positive relationship. With a 0.05 significance level, the result of rcount = 0.562 from N = 40 and a 1% error level, it can be stated that rcount rtable. As a result of this survey, it has been determined that there is a correlation between online study and student interest-based learning. With a high degree of interpretation, the online study does not affect student motivation to learn.